Housing wealth, mortgages and Australians’ labour force participation in later life - ViforJ, Rachel; Wood, Gavin; Cigdem, M. (SAGE PUBLICATIONS LTD, 2021)
In the life cycle model of consumption and saving, homeownership is an important vehicle for horizontal redistribution. Households accumulate wealth in owner-occupied housing during working lives before benefiting from imputed rent streams in retirement. But in some countries housing wealth’s welfare role has broadened as owners increasingly use flexible mortgages to smooth consumption during working lives. One consequence is higher outstanding mortgages later in life, a burden exacerbated by high real house prices that compel home buyers to demand mortgages that are a growing multiple of their incomes. We investigate whether these developments are prompting longer working lives, an idea that is especially relevant in countries offering relatively low government pensions. Australia is one such country. We use the 2001–2017 panels of the Household, Income and Labour Dynamics in Australia Survey to estimate hazard models of exits from the Australian labour force as workers approach pensionable age. We find that those with high outstanding mortgage debts are more likely to postpone retirement, as are those with relatively low amounts of private pension wealth. These results are stronger in urban housing markets, and especially among males.